STUDY OF THE EFFECTS OF EUGENIC ACID IN ARTHRITIS AND DIABETES MELLITUS IN EXPERIMENTAL RATS - Dr. Rajesh R. Patil; Dr. Gaurav Kumar Sharma; Mr. Rajesh Kumar Sinha; Mrs. Vineeta Chourasia (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Systemic inflammatory burden in rheumatoid arthritis (RA) has been shown to predispose to developing both insulin resistance and type 2 diabetes mellitus (DM). Polypharmacy with cumulative side effects are common problems met with in these medical situations of combined diseases. Aim of the work: the present study evaluates the potential role of Eugenic Acid as a natural product with anti-inflammatory and hypoglycemic activities in combating both DM and RA in experimental animals. Materials and methods: Twenty four male albino rats were used. Eight male rats were used as a normal control group received saline (group1). Arthritis was induced in 16 male albino rats by intradermal injection of 0.1 ml of Freund’s Complete Adjuvant (FCA) in the right hind paw then diabetes induced by alloxan (arthritic and diabetic animals). Animals were divided into 2 groups. Arthritic and diabetic control received sesame oil oral (group 2). Arthritic and diabetic animals treated with Eugenic Acid 100 mg/kg/day orally (group 3). Treatment was started with Eugenic Acid after diabetes induction for two weeks. Results: arthritic and diabetic control animals showed significant elevation in serum level of C-reactive protein (CRP), nitric oxide (NO), malondialdehyde (MDA) tumor necrosis factor-α (TNF-α), hyperglycemia and dyslipidemia compared to normal control group. Treatment with Eugenic Acid exhibited significant reduction in serum level of CRP, NO, MDA, TNF-α, blood glucose level, triglycerides, total cholesterol and LDL compared with arthritic diabetic control group. There was insignificant change in HDL serum level. Conclusion: These results suggested that dietary supplementation with Eugenic Acid could beneficially treat hyperglycemia and dyslipidemia. Also, Eugenic Acid ameliorates RA and could be useful as a beneficial supplement in treatment of RA and DM.